A Systematic Literature Review: Factors Affecting Earnings Management - Anggun Dwi Lestari; Intan Putri Suryati; Warti Asih Febriyanti; Putri Maharani (Systematic Literature Review Journal, 2025)
Earnings management is a form of deviation in the process of preparing financial statements, namely affecting the level of profit displayed in the financial statements. This study aims to identify and analyze the factors that influence earnings management, namely Solvency, Corporate Social Responsibility , Profitability, and Company Size based on the findings of previous studies . The method used is the Systematic Literature Review (SLR). Data collection related to similar research was obtained from 50 journals from the Google Scholar database with a publication year range of 2023-2025. The results of this study indicate that the factors that have a significant effect on earnings management, namely Solvency, have an effect on earnings management. The greater the level of this solvency ratio , the greater the opportunity for managers to carry out earnings management so that the company can more easily obtain funds from creditors. Corporate Social Responsibility influence on earnings management. Improving sustainability performance through CSR by companies can encourage management to take higher earnings manipulation actions. Profitability influences earnings management. When the higher the profits earned by the company, the higher the Earnings Management practices carried out by the managers. Company ​size influences earnings management. The larger the size of a company, the smaller the opportunity to carry out earnings management.